Analysis of Courses and Teacher Training Programs on Playful Methodology in Andalusia (Spain) - Lina Higueras-Rodríguez; Marta Medina-García; Enriqueta Molina-Ruiz (MDPI AG, 2020)
In this study we analyzed the primary teaching and training experiences that observe play as a didactic resource to facilitate learning, highlighting fundamental elements and characteristics. A descriptive analysis of the different programs and contents with respect to playful methodology proposed by the Ministry of Education of Andalusian Government (Spain) is presented. The purpose of this type of descriptive idiographic research is to define, classify, catalogue, or characterize the experiences of innovation and projects on ludic methodology. The results show a total of 217 experiences and programs that deal with the use of playful methodology in the classroom. The results conclude that there are training resources interested and involved in the training of teachers in relation to play as a didactic resource. This type of training is carried out outside the university environment and has the characteristics of permanent training.